The Effect of Plyometric Training up and downstairs and obstacle jumping on the improvement of squat style long jump results for male participants in the DKI Jakarta Athletic Club - Mohammd Fathan Mubina; Moch. Asmawi; Heny Widyaningsih (Gladi : Jurnal Ilmu Keolahragaan, 2021)
The objectives of this study were 1) To improve the hurdle jumping training on the long jump results of the squat style in the male participants of the DKI Jakarta club. 2) Increasing the plyometric training up and downstairs to the results of the squat-style long jump in the male participants of the DKI Jakarta club. 3) This is more influential between the plyometric training of hurdle jumping and plyometric training up and downstairs to improve the squat style long jump results for male participants in the DKI Jakarta club. The method to be used is an experimental method, namely the research design using "(Pre-Test and Post Test Two Group Design (pretest-posttest randomized group design)", namely to determine the independent and dependent variables (Ronny, 2007: 138). The initial and final tests using the hurdle jump obtained an average deviation of MD = 0.26 standard deviation SD = 0.07 and the standard error mean SEMD = 0.03 these results produce at-table at degrees of freedom (DK) = 5-1 = 4 with a significant level 5% obtained the critical value of t-table = 2.776 with these results, then H0 is rejected because t-count = 7.63 which means that t-count ≥ t-table then H0 is rejected and Ha is accepted, where the hypothesis is Ha = there is an increase in obstacle jump training to the long jump results squat style on club athletes in DKI Jakarta.